Penerapan Metode Praktik pada Pelatihan Menyulam Benang Emas di PKBM Ar-Raudah Naras 1 Kota Pariaman - Ulfa Liana Putri; Jamaris Jamna (Universitas Negeri Padang, 2018)
Background of this research is motivated by the success of a gold thread embroidery program in PKBM Ar-Raudah Naras 1 Kota Pariaman. This was evidenced by the increasing number of learning citizens from year to year, the high enthusiasm of the learning community and the high enthusiasm of the residents to learn to embroider gold thread training activities. This research is a descriptive study, with a population of learning population totaling 32 people, the sample was taken 72% of the population, namely 22 people with a sampling technique that is simple random sampling. Techniques using questionnaires, and data collection tools using questionnaires. Data analysis techniques use a percentage formula. The results showed that the implementation of the practice method in the initial activity was very good category, the application of the practice method in the core activities was very good category, and the application of the practice method in the category evaluation activity was very good. It is suggested to Instructors to improve the application of practice methods on initial activities, core activities and evaluation activities, and for other researchers to be able to examine other factors that have not been examined in this study relating to the application of practice methods.Keywords: Practice Method, Embroider Training